Effect of tunnel ventilation and evaporative cooling on the barn environment and cow comfort in midwest dairy facilities - John F. Smith; Joseph P. Harner; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2002)
During the summer of 2001 six tunnel ventilated tie stall barns in northeastern Missouri and southeastern Iowa were evaluated. Three of the barns were equipped with cellulose evaporative pads and three were not. Temperature and relative humidity were recorded continuously for 11 weeks from July 1 to September 15, 2001. Cattle housed in tie stall barns equipped with evaporative cooling had lower average respiration rates (65.7 vs 70.3 breaths/min) than those housed in barns without evaporative cooling. However, rates observed in the morning and at night were not different, only the afternoon rates differed significantly. Average rectal temperatures were also lower for the cows housed in evaporative cooled barns. Similar to respiration rates, the greatest differences existed during the afternoon. Skin temperatures followed respiration rates and rectal temperatures and were significantly lower for the cattle housed in the barns equipped with evaporative cooling with the greatest differences observed during the afternoon. Barns equipped with evaporative cooling pads were up to 8.25ºF cooler during the afternoon hours than those without. However, relative humidity increased up to 30% and THI decreased up to 3.25 units over ambient conditions. As compared to the barns with only tunnel ventilation, barns with evaporative cooling had a greater percentage of July and August hours at a THI level below 70 and eliminated the hours in the 85-90 THI level during the hours of 1:00 PM and 8:00 PM. Evaporative cooling reduced the heat stress during the afternoon hours without increasing the stress during the evening and night hours as compared to the tunnel ventilated barns. This study showed significant advantages for the evaporative cooled and tunnel ventilated barns in terms of respiration rates, rectal temperatures and barn environment.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; Heat abatement; Facilities; Stress